The doctoral research abstracts Vol:1 2012 / Institute of Graduate Studies, UiTM - Universiti Teknologi MARA, Institute of Graduate Studies (Institute of Graduate Studies, 2012)
Foreword: Congratulations to Institute of Graduate Studies on the 1st issue of The Doctoral Research Abstracts. This inaugural issue consists of 40 abstracts from our PhD graduands receiving their scrolls in the UiTM’s 76th Convocation. This convocation is very significant especially for UiTM since we are celebrating the success of 40 PhD graduands from 12 of the university’s 25 faculties – the largest number ever conferred at any one time. To the 40 doctorates, I would like it to be known that you have most certainly done UiTM proud by journeying through the scholastic path with its endless challenges and impediments, and by persevering right till the very end. Let it remain in your thoughts and hearts that knowledge is Godgiven, and for those of us who have some to spare, never fear to share with those around us, and never be sparing in serving the community and the country, in the name of the Almighty.